Ballot design and invalid votes: Evidence from Colombia (2017)
We examine the tendency for complex ballots to undermine the ability of voters to cast valid votes. Specifically, we investigate the role of ballot design plays in explaining the high rate of invalid votes in Colombia observed in 2007. We address this question first by looking at data from a study observing the use of alternate ballot designs in a controlled environment, varying the information voters have when attempting to cast the ballot. Our results show that there is an effect of the ballot design on the amount of invalid votes and that this effect varies with socio-demographic characteristics, such as education. We then examine the observed pattern of invalid votes in Colombia before and after the implementation of the ballot redesign. Our results suggest that the introduction of a ballot with improved usability was associated with a significant decline in the number of invalid votes and that a rural-urban difference observed before the new ballot was no longer present. © 2017 Elsevier Ltd